Assessment Virtual Test (ASVITE): Assessment Virtual Based on Interactive Lecture Demonstration (ILD) to Support Employability Skills - Kissi Marwanti; Suherman Suherman; Firmanul Catur Wibowo; Dina Rahmi Darman; Yudi Guntara (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2020)
The development of information and communication technology (ICT) based on computer technology offers another alternative to an assessment form. In supporting employability skills, the assessment format can be presented in an assessment combined with animation. This study aims to develop a virtual test assessment (ASVITE) based on Interactive Lecture Demonstration ( IL D) to support 21st-century competence of employability skills. This study uses an R&D method with a modification of the 4D development model, consisting of define, design, develop, and disseminate. Product developed in the form of tests ASVITE the objective test with four possible answers animation associated with the optical material. The results of the judgment by experts in physics material obtained 18 valid questions, and based on ICT experts, an average value of 84,17% was collected with the category "Very Eligible" in supporting employability skills. The instrument trial results obtained an average value of 83.4% with the grade "Very Good" based on student responses. ILD-based ASVITE can support employability skills.